The First 1000 Days of Early Childhood Becoming - Gradovski, Mikhail; Ødegaard, Elin Eriksen; Rutanen, Niina; Sumsion, Jennifer; Mika, Carl; White, E. Jayne (Policy and Pedagogy with Under-three Year Olds: Cross-disciplinary Insights and Innovations, 2019)
XII, 148 p.